Evaluation of Spatial Satisfaction in Administrative Environment of Art Galleries - Korjani, Sheida; Akbari Namdar, Shabnam (European Journal of Sustainable Development, 2018)
Contemporary art galleries and museums are now facing a new market with many and varied visitors, who are differently motivated and have different expectations. In most cases, renovated historic buildings face significant challenges in provision of suitable administration layout for the staff. This study was intended to provide applicable information for design and management of effective workplaces in renovated art galleries and museums by a survey on five galleries and museums. The results revealed that renovation in the office environment of renovated historic buildings converted to galleries and museums have improved the amount of work-surface, function of furniture, amount of storage, function of storage, and style of furniture. Besides, the analysis showed that the open floor plan of a work environment in art galleries, over time, is a source of noise problems and deprives office workers of privacy and personalized area. Keywords: building, gallery, satisfaction, sustainability